Building executive information systems and other decision support applications - Watson, Hugh J. (John Wiley and Sons, 1997)
An introduction to EIS. An EIS development framework. Understanding executives, their work, and information needs. Gaining executive commitment. Assembling the EIS staff. Determining the need. Determining the information requirements...